2020
DOI: 10.9755/ejfa.2020.v32.i9.2147
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different nutritional treatments on maize hybrids morphological traits based on stability statistical methods

Abstract: This study investigates the sustainability of agriculture in the context of the various debates that have occurred about agriculture, its elements, and functions. One of the main breeding programs aims to achieve stable and high yield varieties in different conditions by studying the effect of genotypes on traits year on year. The study investigates the effect of genotypes on grain yield traits in two hybrids (FAO340 and FAO410) planted in a completely randomized block design with four replications for two yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…It makes it possible to examine the relationships between the environments and identify the target environments in breeding plans [11]. This model was applied when studying the genotype interacting with the environment in wheat [12], barley [13,14], and maize [15][16][17][18][19][20][21][22]. In a study during two years for 10 regions on the stability of Chinese maize hybrids grain performance, Fan et al [18] used the GGE biplot and other stability statistics.…”
Section: Introductionmentioning
confidence: 99%
“…It makes it possible to examine the relationships between the environments and identify the target environments in breeding plans [11]. This model was applied when studying the genotype interacting with the environment in wheat [12], barley [13,14], and maize [15][16][17][18][19][20][21][22]. In a study during two years for 10 regions on the stability of Chinese maize hybrids grain performance, Fan et al [18] used the GGE biplot and other stability statistics.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the mean of Duncan method genotypes under normal and stress conditions showed that KSC707, SC301 and KSC704 genotypes had better performance than other hybrids in all evaluated traits, respectively. Additionally, the DC307 genotype under normal conditions and the KSC400 genotype under stress conditions were identified as hybrids with low yield and rank ( Table 2 ), Mousavi et al [ 22 ]. In their experiments under normal humidity conditions, the KSC704 genotype had the highest yield compared to other hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…In many studies, fertilizer's positive effect emphasized raising grain yield, the number of kernels in an ear, and kernel value in different corn genotypes. Fertilizer causes proliferation of the leaf number, leaf size and width, and the plant's dry matter [35][36][37][38][39][40][41]. The number of seeds per row had a minimum effect for treatments and low stability in terms of GGE analysis.…”
Section: Discussionmentioning
confidence: 99%